One Night on Call: A Simulation Exercise for New Interns - Dale Vincent; Benjamin Berg (Association of American Medical Colleges, 2009)
Abstract This resource consists of material for a single, half-day manikin-based simulation course for fourth-year medical students nearing the end of medical school, or new interns. The course consists of six scenarios that depict common inpatient situations encountered by house staff on call during their first month of residency. We surveyed all participants at the end of each simulation session with 105 responding. The course was well received. Sixty-six percent of the participants were in their last month of medical school. Thirty-four percent of the participants were interns within two weeks of July 1st. The interns were distributed between surgery (25%), medicine (19%), pediatrics (14%), family medicine (13%), OB-GYN (11%), psychiatry (11%), and other (7%). The first groups consisted of about 18 learners and four faculty members, and used four manikins. Control of session was improved when the group size was reduced to about 12 learners and three faculty members, using three manikins. Interactivity was improved, while retaining some group efficiencies.